2022
DOI: 10.1590/01047760202228012967
|View full text |Cite
|
Sign up to set email alerts
|

Pine afforestation improves the biological soil attributes linked to methane oxidation in a temperate zone of Argentina

Abstract: Background: Atmospheric methane (CH 4 ) is responsible for approximately 20% of global warming since the preindustrial era. Forests are land ecosystems whose role is crucial for mitigating the greenhouse effect due to their capacity to capture and store C and preserve other processes such as CH 4 oxidation in the soil. On the other hand, in the particular case of afforestation, there are contradictory results about the magnitude of CH 4 uptake variation due to changes in methanotrophic bacteria activity and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Several studies show that [CH 4 ] drops to values less than 50% of C 0 below 20 cm depth in various land uses (crops, pastures, grasslands, afforestation) (De Bernardi et al., 2019; Nan et al., 2020; Price et al., 2003; Wang et al., 2014; Wu et al., 2010) as it was observed in this work too. Moreover, it is between 5 and 15 cm depth where the largest methanotrophic activity is located (Terán et al., 2022), coinciding with the highest decrease in [CH 4 ] measured along the soil profile for all studied land uses (Figure 3); [CH 4 ] only decreased 10% of C 0 in A, but 20% in NG and between 20% and 30% in the afforested sites coinciding with differences in the magnitude of CH 4 uptake between land uses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that [CH 4 ] drops to values less than 50% of C 0 below 20 cm depth in various land uses (crops, pastures, grasslands, afforestation) (De Bernardi et al., 2019; Nan et al., 2020; Price et al., 2003; Wang et al., 2014; Wu et al., 2010) as it was observed in this work too. Moreover, it is between 5 and 15 cm depth where the largest methanotrophic activity is located (Terán et al., 2022), coinciding with the highest decrease in [CH 4 ] measured along the soil profile for all studied land uses (Figure 3); [CH 4 ] only decreased 10% of C 0 in A, but 20% in NG and between 20% and 30% in the afforested sites coinciding with differences in the magnitude of CH 4 uptake between land uses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in the same Pinus plantations have already reported higher CH 4 uptake and a potential biological contribution (i.e. methanotrophic activity) under this land use than under grassland and cropland (De Bernardi et al., 2021; Terán et al., 2022). This work aimed to contribute with new data about land‐use change effects on CH 4 flux measurements in two periods of one‐year long (non‐ consecutive) in four land uses located in a temperate region of the Southern Hemisphere in order to grow global knowledge.…”
Section: Introductionmentioning
confidence: 89%